Pengembangan Kemasan Zero Plastic serta Label Sehat-Halal Produk Tahu dan Tempe - Satria Bangsawan; MS Mahrinasari; Fitria Saftarina; Maristiana Ayu; Susilawati Susilawati (Penerbit Goodwood, 2021)
Purpose: Home industry of tahu and tempe products plays a role in developing economic growth, especially in Bandarlampung City, Indonesia. However, its non-degradable plastic packaging creates harmful environmental effects. In line with this, certified halal-healthy labeling required by Muslim consumers. Therefore, this community service aimed to help the tahu and tempe entrepreneurs in Gunung Sulah Village, Bandarlampung city to know, be aware, and understand the role of zero plastics packaging and certified halal-healthy labeling through training and coaching program. Method: The method used is training and coaching, and then followed by monitoring and evaluation. Results: The results show that knowledge, awareness, and understanding insights of the tahu tempe entrepreneurs increase after joining the training and coaching programs. Conclusion: The entrepreneurs need the alternative zero plastic packagings and are aware that certified halal-healthy labeling is essential to show in the packaging so that the market extends to the modern market; consequently, market share and competitive advantage can improve.